2021
DOI: 10.1016/j.gexplo.2020.106659
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements leaching from Pb Zn mine waste (Plombières, Belgium) and environmental implications

Abstract: The geochemical and mineralogical characterization of mine waste provides essential information to understand the environmental and health impacts and to adequately manage present and historical mine waste sites. In the present study, mine waste samples from a former Zn-Pb mining site were subjected to different types of leaching tests, an in-vitro bioaccessibility test, and a mineralogical analysis. The samples were characterized by elevated pseudo-total Pb (up to 51,800 mg/kg), Zn (up to 60,100 mg/kg), Cd (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…This was confirmed by the macroscopic description of the materials made during the sampling campaign, and by the shapes and textures observed by scanning electron microscopy (SEM) (Figure 10c). Helser and Cappuyns (2020) came to the same conclusion about the amorphous phases being slags when studying materials from Plombières [8].…”
Section: Mineralogy Of Plombières Materialsmentioning
confidence: 80%
See 3 more Smart Citations
“…This was confirmed by the macroscopic description of the materials made during the sampling campaign, and by the shapes and textures observed by scanning electron microscopy (SEM) (Figure 10c). Helser and Cappuyns (2020) came to the same conclusion about the amorphous phases being slags when studying materials from Plombières [8].…”
Section: Mineralogy Of Plombières Materialsmentioning
confidence: 80%
“…They concluded that the highest leaching of metal(loid)s occurred under acidic and highly alkaline conditions, while metal(loid) leaching was low in neutral and alkaline conditions. The highly acidic and alkaline pHs are not likely to occur in a natural environment [8], and therefore, the potential for acidic and metal-rich waters leaching from the Plombières mine site is low. Overall, the mineralogical results are consistent with the geochemical analyses for all material types.…”
Section: Mineralogy Of Plombières Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlations between the leachable water-soluble Pb and Zn with the exchangeable, labile phases and the total content suggests that the release of Pb and Zn into the environment from the SPs was mainly attributed to the exchangeable phase and not so much from the total content of Pb and Zn (Figures S2 and S3). In addition, the Pb bound to carbonate phase is usually influenced by the pH of the environment; for example, under gastric conditions, cerussite (PbCO3) might significantly dissolve in the acidic conditions [43], which increases the bioaccessibility of ingested PTEs. However, the present study could not identify the host minerals for the PTEs; electron microprobe analysis might be a possible approach to identifying the mineral phases [44].…”
Section: Discussionmentioning
confidence: 99%